Differences in the relationships between interoceptive sensibility and self-objectification in women with high and low body dissatisfaction: A network analysis. - Akansha Mahesh Naraindas; Amy McInerney; Sonya Deschênes; Sarah Maeve Cooney (PLoS ONE)
Body dissatisfaction is a normative experience with the potential to impact women's mental and physical health. It is closely related to self-objectification, where the body is viewed as an object for aesthetic evaluation rather than for its functional attributes. Self-objectification not only affects women's body image but is associated with diminished subjective awareness of, and attention towards, internal bodily states (i.e., interoceptive sensibility). This study uses network analysis and network comparison to investigate the relationships between features of interoceptive sensibility and self-objectification in women with high (N = 348) and low (N = 354) body dissatisfaction. The results firstly revealed significant differences in the connections between interoceptive sensibility and self-objectification in women with high and low body dissatisfaction (p = 0.026). High body dissatisfaction in women was characterised by lower levels of body listening, self-regulation, and body trusting. Alternatively, high emotional awareness was most central to women with low body dissatisfaction. This study highlights the central role of interoceptive sensibility in body dissatisfaction and identifies key features of interoceptive sensibility to target for improving body dissatisfaction.